Optimal Portfolio Using Single Index Model and Alpha Jensen for Best Investment Alternative (Study on IDX30, BISNIS27, and INVESTOR33 Stocks on the Indonesia Stock Exchange 2017-2019 Period) - Arinda Sasmita Rahma; Muhammad Saifi; Nila Firdausi Nuzula (Sekolah Pascasarjana Universitas Brawijaya, 2022)
This study aims to determine the stocks incorporated in the IDX30, BISNIS27, and INVESTOR33 indexes that form an optimal portfolio based on a single index model and Alpha Jensen to measure portfolio performance. The research method used is descriptive with a quantitative approach and secondary data sources from the Indonesia Stock Exchange. The population used is the IDX30, BISNIS27, and INVESTOR33 index stocks for the period 2017 – 2019, based on the established criteria, 19 stocks are obtained as the IDX30 sample, 14 stocks as the BISNIS27 sample, and 26 stocks as the INVESTOR33 sample. In 2017 and 2018, from the calculation of Jensen's alpha index value and the Expected Return Portfolio value based on the calculation of the Single Index Model, the BISNIS27 Index has the highest value compared to the IDX30 index and the INVESTOR33 index. While in 2019, the IDX30 Index had the highest value, and the BISNIS27 Index had the lowest value. Although the IDX30, BISNIS27, and INVESTOR33 indexes are included in one sub-classification of the liquidity index, namely those with high transaction liquidity, they have different performances. Keywords: single index model, optimal portfolio composition, alpha jensen